Organized Sport Participation From Childhood to Adolescence Is Associated With Bone Mass in Young Adults From the Raine Study - McVeigh, Joanne; Howie, E.; Zhu, K.; Walsh, J.; Straker, Leon (American Society for Bone and Mineral Research, 2018)
© 2018 American Society for Bone and Mineral Research There is a critical need for longitudinal cohort studies to consider the association of the cumulative exposure of physical activity during childhood and adolescence and bone mass. The aim of this study was to investigate the relationship between organized sports trajectories (that capture distinct and potentially meaningful patterns over critical developmental periods) and bone mass at age 20 years. Participation in organized sport was recorded by parental report at ages 5, 8, 10, 14, and 17 years in 984 offspring (48% female) of a pregnancy cohort (Raine Study). Latent class analysis identified three trajectory classes in each sex. In females, these were “consistent sport participators” (48%), “dropouts” (34%), and “non-participators” (18%); in males, “consistent sport participators” (55%), “dropouts” (37%), and “sport joiners” (8%). Whole-body bone mineral content (BMC) at age 20 years was assessed by dual-energy X-ray absorptiometry (DXA). At age 20 years, after adjustment for covariates measured at age 20 years, including height, lean mass, physical activity, calcium intake, serum 25-hydroxyvitamin D, alcohol, and smoking, males who were “consistent sport participators” had significantly greater whole-body and leg BMC than those who dropped out of sport (p < 0.001), whereas males who joined sports had significantly greater leg BMC than those who dropped out of sport (p = 0.002). Females in the “consistent sport participator” trajectory had significantly greater leg BMC than those who dropped out (all p = 0.004). Participation in organized sport during childhood and adolescence is associated with bone mass at age 20 years. Because attainment of optimal peak bone mass in young adulthood is protective against osteoporosis in later life, this may have long-term skeletal benefits. © 2018 American Society for Bone and Mineral Research.